ADMINISTRASI KELOMPOK TANI DI KECAMATAN TOMOHON UTARA, KOTA TOMOHON - Daisy ., Sumilat; Grace A. J. Rumagit; Welson M. Wangke (AGRI-SOSIOEKONOMI, 2017)
The study aims to determine the completeness of the administration of farmers' groups in North Tomohon Sub-district, Tomohon City. The research was conducted from July to September 2016. The data were used primary data. Sampling method on three (3) groups of farmers in the district of North Tomohon is done by purposive sampling. The variables in this study are the characteristics of the board of farmer group organizations (Chairman, Secretary, and Treasurer), characteristics of the farmer group (the name of the farmer groups, year of farmer groups established, and the number of members of farmer groups) and administrative group books. The administration books have two main parts: the books of administrative activities and the books of administration finance. The analysis used for variable administrative and financial administration which each answer is associated with a form of the statement expressed by the words that Good was given Score: 3, Less Good granted Score: 2 and No Good granted Score: 1. The results of this research farmer group that is located relatively far from BP3K Office have good administrative requirements compared to the farmer group that is located very close to BP3K Offuce. That's because a group of farmers near BP3K office has motivation to get funding and the lack of cooperation among the board members in addition to the lack of visitation held by agriculutere extension staf, while the farmer groups that located far from BP3K Office has established with motivated to increase the welfare of members of farmers, the board members has good cooperation and good management. It is also the group always get the attention of the agriculutre extension staf by holding regular visitation to the farmer groups and therefore contributes positively to the administrative requirements for farmers' groupsKeywords: administration, farmers group, North Tomohon Sub-district, Tomohon City